Effect of acute respiratory infections in infancy on pulmonary function test at 3 years of age: a prospective birth cohort study. Issue 1 (19th February 2020) - Kumar, Prawin; Mukherjee, Aparna; Randev, Shivani; Medigeshi, Guruprasad R; Jat, Kana Ram; Kapil, Arti; Lodha, Rakesh; Kabra, Sushil Kumar
Abstract : Introduction: Acute respiratory infections (ARIs) in infancy may have a long-term impact on the developing respiratory system. We planned a prospective cohort study to determine the impact of ARI during infancy on the pulmonary function test indices at 3 years of age. Methods: A cohort of normal, full-term newborns were followed up 6 monthly and during ARI episodes. Infant pulmonary function tests (IPFTs) were performed at baseline and each follow-up visit using tidal breathing flow-volume loop, rapid thoracoabdominal compression (RTC) and raised volume RTC manoeuvres. During each ARI episode, nasopharyngeal aspirates were tested for respiratory pathogens by real-time PCR. Results: We screened 3421 neonates; 310 were enrolled; IPFT was performed in 225 (boys: 125 (55.6%)) at 3 years. During infancy, 470 ARI episodes were documented in 173 infants. At 3 years, children with history of any ARI episode during infancy had lower forced expiratory volume in 1 s (FEV1.0 ), forced expiratory volume in 0.75 s (FEV0.75 ), forced expiratory volume in 0.5 s (FEV0.5 ), forced expiratory flow between 25% and 75% of FVC (FEF25–75 ), and maximal expiratory flow at 25% of FVC (MEF25 ) as compared with those without any ARI episode during infancy. The ratio of tidal expiratory flow (TEF) at 25% or 50% of tidal expiratory volume to peak TEF (TEF50 or TEF25 /peak TEF) at 3 years was significantly increased in children who had ARI in infancy. Conclusions: ARI during infancy is associated with impaired pulmonary function indices such as increased resistance and decreased forced expiratory flow and volume at 3 years of age.